2021
DOI: 10.1002/smtd.202001308
|View full text |Cite
|
Sign up to set email alerts
|

All‐Inorganic Lead‐Free Perovskite(‐Like) Single Crystals: Synthesis, Properties, and Applications

Abstract: Due to their nontoxicity, stability, and unique optoelectronic properties, all‐inorganic lead‐free halide semiconductors with perovskite and perovskite‐like structures have successfully emerged as promising optoelectronic materials for various applications, such as solar cells, light‐emitting diodes (LEDs), photodetectors, and X‐ray detectors. To further explore their practical potentials, researchers have paid more attention in all‐inorganic lead‐free perovskite (‐like) (ILFP) single crystals. For these singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 143 publications
(187 reference statements)
0
63
0
Order By: Relevance
“…In recent years, organic-inorganic hybrid perovskites, as a new multifunctional material with diverse structures and lowcost solution processability, have attracted particular attention for their dramatic advances in photovoltaic devices, solid-state lighting and displays. [17][18][19][20] The general chemical formula of a classic lead halide perovskite is APbX 3 , where A is a monovalent cation such as Cs + , methylammonium (CH 3 NH 3 + ), formamidinium (HC(NH 2 ) 2 + ) or methylhydrazinium (CH 3 NH 2 NH 2 + ) and X is a halide ion. [21][22][23] Lead is known to be toxic and degrades slowly, which would hinder its commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, organic-inorganic hybrid perovskites, as a new multifunctional material with diverse structures and lowcost solution processability, have attracted particular attention for their dramatic advances in photovoltaic devices, solid-state lighting and displays. [17][18][19][20] The general chemical formula of a classic lead halide perovskite is APbX 3 , where A is a monovalent cation such as Cs + , methylammonium (CH 3 NH 3 + ), formamidinium (HC(NH 2 ) 2 + ) or methylhydrazinium (CH 3 NH 2 NH 2 + ) and X is a halide ion. [21][22][23] Lead is known to be toxic and degrades slowly, which would hinder its commercial applications.…”
Section: Introductionmentioning
confidence: 99%
“…reported that 0D Cs 4 EuX 6 showed excellent scintillation properties under the excitation of gamma‐ray. The high scintillation yield for Cs 4 EuBr 6 was reported as 78000±4000 photons/MeV under 137 Cs gamma‐ray irradiation, which is better than that of the commercial scintillator NaI:TI and among the highest self‐activated scintillators so far [21] …”
Section: Emerging Applications For 0d Metal Halidesmentioning
confidence: 95%
“…In recent years, the synthesis is mainly directed to wet‐chemistry techniques due to lower cost and better accessibility. By proper selection of solvents and precursor chemicals, wet‐chemistry methods can be readily adapted to synthesize various 0D metal halides with controllable sizes down to several nanometers [21] . The wet‐chemistry synthesis of current interest mainly includes antisolvent method, coprecipitation method, hot injection method.…”
Section: Synthesis Of 0d Metal Halidesmentioning
confidence: 99%
“…In terms of structure, Pb 2+ cations are separated by six neighbor X-site anions to bulid Pb-X octahedrons, which corner-share with each other to constitute the main frame and A + intercalates the voids [24]. The replacement of Pb 2+ with lead-free ions results in both the deformation in nanoscale structure and the conversion of properties because of the differences in chemical valence and ion size [23]. Therefore, LFPSCs exhibit plenty of novelty and diversity, we discussed several typical LFPSCs in this section and summarized in Table 1, along with the schematic diagrams of synthesis methods as shown in Figure 1.…”
Section: Various Systems Of Pb-free Single Crystalmentioning
confidence: 99%
“…Though a number of efforts have been devoted to develop various LFPCs, a lack of comprehensive understanding towards the synthesis methods, properties, and the device performance still restrict their practical application. To promote the development of LFPSCs, we mainly focus on summarizing the up-to-date advancement of several representative PSCs and their applications in photodetectors, photovoltaics solar cells, X-ray detectors, light-emitting diodes (LEDs), and other devices [23]. To be specific, various systems including replacement of Pb-based perovskites, perovskite-like derivate and double perovskites are presented.…”
Section: Introductionmentioning
confidence: 99%